FACTORS LIMITING THE EFFECTIVENESS OF INTESTINAL PARASITOSES' PHARMACOTHERAPY - Kalina Stoyanova; Tatyana Cvetkova; Stela Dragomanova; Stoyan P. Pavlov (Peytchinski Publishing, 2017)
The effective etiological antiparasitic treatment fulfils two major goals - to cure the infected patient and to terminate its role as an epidemiologically relevant source of infection. The purpose of this study is to evaluate the effectiveness of the pharmacotherapy against the most common intestinal helminthic and protozoal infections diagnosed in Varna region. Material and Methods: 879 patients with laboratory-confirmed intestinal parasitoses were treated etiologically with the established anthelminthic and antiprotozoal agents. Mandatory and active post-treatment laboratory monitoring served as the basis for the assessment of the therapy effectiveness. Results: Enterobiasis has the highest prevalence of the intestinal parasitic infections with estimated treatment success of 94,7% at the end of the mandatory period and nearly 100% at the end of our monitoring. The significantly greater rate of relapses was registered among the patients with the two most common protozoal invasions - Giardiasis (9,5%) and Blastocystosis (6,7 %). Our analysis established that the main factors limiting the effective antiparasitic pharmacotherapy are extraneous, i.e. independent of the pharmacological properties of the agent or parasite's biology. The most prominent reasons for therapy failure are poor or missing compliance to the therapy regimen, inadequate form or dosage of the medication, unrecognized source of (re)invasion, etc. In conclusion, the collaboration between the general practitioners, clinical parasitologists and respectively the patients themselves is crucial for achieving an effective therapy and the resultant control of the intestinal parasitoses.